2020
DOI: 10.1002/aoc.6017
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) complex intercalated graphene oxide nanocomposites as versatile, reusable catalysts for click reaction

Abstract: In this work, we report the efficient, high stable copper(II) complexes intercalated graphene oxide (GO) used as green catalysts for copper(II) complex mediated click reaction. Copper(II) Bis(2,2′‐bipyridine) [CuII (bpy)2] (C1) and Copper(II) Bis(1,10‐phenanthroline) [CuII (phen)2] (C2) have synthesized for the intercalation of corresponding nanocomposites with GO, [GO@CuII (bpy)2] (GO‐C1) and [GO@CuII (phen)2] (GO‐C2). The noncovalent interaction of complexes supported on the surface of the GO nanosheets prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Hamed et al have Cu(II)-metformin immobilized on graphene oxide as an efficient and recyclable catalyst for the Beckmann rearrangement (Solaiman Hamed and Mohammad Ali, 2020). In our earlier work, we have reported the highly stable copper(II) complex-intercalated GO nanocomposite as the heterogeneous copper catalyst for the CuAAC reaction and the desired 1,4disubstituted 1,2,3-triazoles were obtained in excellent yield (Samuel et al, 2020). The aim of the present work is to develop a heterogeneous, efficient, nanomaterial catalyst, caging the copper complex over the GO surface for the usage of click reaction in the biological substrates in aqueous medium, upon the reduction of Cu(II) complex-GO composites.…”
Section: Introductionmentioning
confidence: 83%
“…Hamed et al have Cu(II)-metformin immobilized on graphene oxide as an efficient and recyclable catalyst for the Beckmann rearrangement (Solaiman Hamed and Mohammad Ali, 2020). In our earlier work, we have reported the highly stable copper(II) complex-intercalated GO nanocomposite as the heterogeneous copper catalyst for the CuAAC reaction and the desired 1,4disubstituted 1,2,3-triazoles were obtained in excellent yield (Samuel et al, 2020). The aim of the present work is to develop a heterogeneous, efficient, nanomaterial catalyst, caging the copper complex over the GO surface for the usage of click reaction in the biological substrates in aqueous medium, upon the reduction of Cu(II) complex-GO composites.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, Cu@βCD-PEG-mesoGO was recovered and recycled up to ten times without any significant decrease in its activity. More recently, Bhagavathsingh et al [115] reported on the bis(2,2 -bipyridine)copper(II) complex supported on GO (GO@Cu(II)-(bpy) 2 ) for the synthesis of 1,4-disubstituted 1,2,3-triazole derivatives. This catalyst was characterized by an XPS analysis that revealed the presence of copper(I) and copper(II) species in GO@Cu(II)-(bpy) 2 with 3.4% of copper loading, as detected by inductively coupled plasma optical emission spectroscopy (ICP-OES).…”
Section: Carbon Material-supported Catalysts For Cuaacmentioning
confidence: 99%
“…Intercalation of copper(II) bis(2,2′‐bipyridine) [Cu(II) (bpy) 2 ] and copper(II) bis(1,10‐phenanthroline) [Cu(II) (phen) 2 ] onto the GO planes [GO@Cu(II) (bpy) 2 ] and [GO@Cu(II) (phen) 2 ] was investigated as a green approach for the preparation of efficient catalysts for “click” reaction. [ 82 ] It should be noted that GO due to its specific features has been integrated in sustainable green chemistry. Van der Waals interactions of bipyridine and phenanthroline ligands of Cu(II) complexes on GO surfaces facilitate the resulting heterogeneous catalyst to provide mass transfer of the organic precursors into desired products in short reaction times.…”
Section: Application Of Copper Modified Graphene Oxide Catalysts For Carbon‐nitrogen Bond Formationmentioning
confidence: 99%